Fishbone Analysis of the Implementation of Adolescent Reproductive Health Programs at Nagrak Public Health Center - Syafriyanti, Willyana; Widiasmara, Mira; Tania Fidzikri, Nanda Berliana (Rifa'Institute, 2025)
Introduction: Adolescent pregnancy has become an increasing concern in the working area of Nagrak Public Health Center, Bandung Regency, over the past three years. In response, a reproductive health program targeting adolescents has been implemented; however, its effectiveness remains suboptimal. 0Objective: This study aims to analyze the root causes of the less-than-optimal implementation of adolescent reproductive health programs at the Nagrak Public Health Center and propose actionable solutions. Method: A qualitative research method with a case study design was employed, conducted between April and May 2025. Data were analyzed using a fishbone diagram to identify contributing factors. Result and Discussion: The findings reveal several challenges: under the